1. Introduction
Let $\mathbb{N}$ be the set of all non-negative integers. For any integer r and m, let $r+m\mathbb{N}=\{r+mk: k\in\mathbb{N}\}$. Let A be the set of all non-negative integers which contain an even number of digits 1 in their binary representations and $B=\mathbb{N}\backslash A$. The set A is called Thue–Morse sequence. For any positive integer l, let $A_{l}=A\cap [0, 2^{l}-1]$ and $B_{l}=B\cap [0, 2^{l}-1]$. For $S\subseteq \mathbb{N}$ and $n\in \mathbb{N}$, let the representation function $R_{S}(n)$ denote the number of solutions of the equation $s+s'=n$ with $s, s'\in S$ and $s \lt s'$. Sárközy asked whether there exist two subsets $C, D\subseteq \mathbb{N}$ with $|(C\cup D)\backslash (C\cap D)|=\infty$ such that $R_{C}(n)=R_{D}(n)$ for all sufficiently large integers n. By using the Thue–Morse sequence, Dombi [Reference Dombi6] answered Sárközy’s problem affirmatively. Later, Lev [Reference Lev10], Sándor [Reference Sándor12] and Tang [Reference Tang17] proved this result by different methods. Partitions of non-negative integers and their corresponding representation functions have been extensively studied by many authors. The related results can be found in [Reference Chen and Tang4, Reference Chen and Wang5, Reference Jiao, Sándor, Yang and Zhou7–Reference Kiss and Sándor9, Reference Sándor12–Reference Tang17, Reference Yang and Chen19].
In 2012, Yu and Tang [Reference Yu and Tang20] began to focus on partitions of non-negative integers with the intersection not empty. They studied the intersection of two sets is an arithmetic progression and posed the following conjecture:
Conjecture 1.1.
Let $m\in\mathbb{N}$ and $R\subset \{0, 1, \ldots, m-1\}$. If $C\cup D=\mathbb{N}$ and $C\cap D=\{r+km: k\in\mathbb{N}, r\in R\}$, then $R_{C}(n)=R_{D}(n)$ cannot hold for all sufficiently large n.
In 2016, Tang [Reference Tang18] obtained the following theorem.
Theorem A [Reference Tang18, Theorem 1]
Let m be an integer with $m\geq 2$. If $C\cup D=\mathbb{N}$ and $C\cap D=m\mathbb{N}$, then $R_{C}(n)=R_{D}(n)$ cannot hold for all large enough integers n.
In 20l6, Chen and Lev [Reference Chen and Lev3] disproved Conjecture 1.1 by the following result.
Theorem B [Reference Chen and Lev3, Theorem 1]
Let l be a positive integer. There exist two sets C and D with $C\cup D=\mathbb{N}$ and $C\cap D=(2^{2l}-1)+(2^{2l+1}-1)\mathbb{N}$ such that $R_{C}(n)=R_{D}(n)$ for every positive integer n.
In [Reference Chen and Lev3], Chen and Lev also proposed the following problem.
Problem 1.2.
Given $R_{C}(n)=R_{D}(n)$ for every positive integer n, $C\cup D=\mathbb{N}$ and $C\cap D=r+m\mathbb{N}$ with $r\geq 0$ and $m\geq 2$, must there exist an integer $l\geq 1$ such that $r=2^{2l}-1, m=2^{2l+1}-1$?
Afterwards, Li and Tang [Reference Li and Tang11], Chen, Tang and Yang [Reference Chen, Tang and Yang2] solved Problem 1.2 under the condition $0\leq r \lt m$. In 2021, Chen and Chen [Reference Chen and Chen1] solved Problem 1.2 affirmatively.
Theorem C [Reference Chen and Chen1, Theorem 1.1]
Let $m\geq 2$ and $r\geq 0$ be two integers and let C and D be two sets with $C\cup D=\mathbb{N}$ and $C\cap D=r+m\mathbb{N}$ such that $R_{C}(n)=R_{D}(n)$ for every positive integer n. Then there exists a positive integer l such that $r=2^{2l}-1$ and $m=2^{2l+1}-1$.
Let $r_{1}, r_{2}, m$ be integers with $0 \lt r_{1} \lt r_{2} \lt m$. In this paper, we focus on partitions of non-negative integers into two sets $C, D$ with $C\,\cup\,D=\mathbb{N}$ and $C\,\cap\,D=(r_{1}\,+\,m\mathbb{N})\cup (r_{2}\,+\,m\mathbb{N})$ such that $R_{C}(n)=R_{D}(n)$ for all $n\in\mathbb{N}$ and obtain the following result.
Theorem 1.3. Let $r_{1}, r_{2}, m$ be integers with $0 \lt r_{1} \lt r_{2} \lt m$ and $2\mid r_{1}$. Then there exist two sets C and D with $C\cup D=\mathbb{N}$ and $C\cap D=(r_{1}+m\mathbb{N})\cup (r_{2}+m\mathbb{N})$ such that $R_{C}(n)=R_{D}(n)$ for all $n\in\mathbb{N}$ if and only if there exists a positive integer l such that $r_{1}=2^{2l+1}-2, r_{2}=2^{2l+1}-1, m=2^{2l+2}-2$.
Motivated by Theorems B and C, we propose the following conjecture for further research.
Conjecture 1.4.
Let $r_{1}, r_{2}, m$ be integers with $0 \lt r_{1} \lt r_{2} \lt m$ and $2\nmid r_{1}$. Then there exist two sets C and D with $C\cup D=\mathbb{N}$ and $C\cap D=(r_{1}+m\mathbb{N})\cup (r_{2}+m\mathbb{N})$ such that $R_{C}(n)=R_{D}(n)$ for all $n\in \mathbb{N}$ if and only if there exists a positive integer l such that $r_{1}=2^{2l}-1, r_{2}=2^{2l+1}+2^{2l}-2, m=2^{2l+2}-2$.
Throughout this paper, let $f(x)=a_{0}+a_{1}x+\cdots+a_{n}x^{n}\in\mathbb{Z}[x]$ and for $m\leq n$, define
For $C, D\subseteq \mathbb{N}$ and $n\in \mathbb{N}$, let $R_{C, D}(n)$ be the number of solutions of $n=c+d$ with $c\in C$ and $d\in D$. Let $C+D=\{c+d: c\in C, d\in D\}$. Let C(x) be the set of integers in C which are less than or equal to x. The characteristic function of C is denoted by
2. Some lemmas
Lemma 2.1. [Reference Chen and Lev3, Lemma 1]
Suppose that $C_{0}, D_{0}\subseteq \mathbb{N}$ satisfy $R_{C_{0}}(n)=R_{D_{0}}(n)$ for all $n\in \mathbb{N}$, and that m is a non-negative integer with $m \notin (C_{0}-D_{0})\cup(D_{0}-C_{0})$. Then, letting
we have $R_{C_{1}}(n)=R_{D_{1}}(n)$ for all $n\in \mathbb{N}$ and furthermore
(i) $C_{1}\cup D_{1}=(C_{0}\cup D_{0})\cup (m+C_{0}\cup D_{0})$;
(ii) $C_{1}\cap D_{1}\supseteq(C_{0}\cap D_{0})\cup (m+C_{0}\cap D_{0})$, the union being disjoint.
Moreover, if $m\notin (C_{0}-C_{0})\cup (D_{0}-D_{0})$, then also in (i) the union is disjoint, and in (ii) the inclusion is in fact an equality. In particular, if $C_{0}\cup D_{0}=[0,m-1]$, then $C_{1}\cup D_{1}=[0,2m-1]$, and if C 0 and D 0 indeed partition the interval $[0, m-1]$, then C 1 and D 1 partition the interval $[0, 2m-1]$.
Lemma 2.2. [Reference Kiss and Sándor8, Claim 1]
Let $0 \lt r_{1} \lt \cdots \lt r_{s}\leq m$ be integers. Then there exists at most one pair of sets (C, D) such that $C\cup D=[0, m], 0\in C, C\cap D=\{r_{1}, \ldots, r_{s}\}$ and $R_{C}( n)=R_{D}(n)$ for every $n \leq m$.
Lemma 2.3. [Reference Kiss and Sándor8, Claim 3]
If for some positive integer M, the integers $M-1, M-2, M-4, M-8, \ldots, M-2^{\lceil \log_{2}M\rceil-1}$ are all contained in the set A, then $\lceil \log_{2}M\rceil$ is odd and $M=2^{\lceil \log_{2}M\rceil}-1$.
Lemma 2.4. [Reference Kiss and Sándor8, Claim 4]
If for some positive integer M, the integers $M-1, M-2, M-4, M-8, \ldots, M-2^{\lceil \log_{2}M\rceil-1}$ are all contained in the set B, then $\lceil \log_{2}M\rceil$ is even and $M=2^{\lceil \log_{2}M\rceil}-1$.
Lemma 2.5. [Reference Kiss and Sándor8, Theorem 3]
Let C and D be sets of non-negative integers such that $C\cup D=[0, m], C\cap D=\emptyset$ and $0\in C$. Then $R_{C}(n)=R_{D}(n)$ for every positive integer n if and only if there exists a positive integer l such that $C=A_{l}$ and $D=B_{l}$.
3. Proofs
Proof of Theorem 1.3. (Sufficiency). For any given positive integer l, let
For given sets $C_{0}=\{0\}, D_{0}=\{1\}$, define
and
It is clear that C 0 and D 0 partition the interval $[0, m_{0}-1]$ and
and $R_{C_{0}}(n)=R_{D_{0}}(n)$ for all $n\in \mathbb{N}$ (both representation functions are identically equal to 0). Applying Lemma 2.1 inductively $2l-1$ times, we can deduce that for any $i\in [0, 2l-1]$, $R_{C_{i}}(n)=R_{D_{i}}(n)$ for all $n\in\mathbb{N}$, the sets Ci and Di partition the interval $[0, m_{i}-1]$ and
In particular, $R_{C_{2l-1}}(n)=R_{D_{2l-1}}(n)$ for all $n\in \mathbb{N}$, the sets $C_{2l-1}$ and $D_{2l-1}$ partition the interval $[0, m_{2l-1}-1]=[0, 2^{2l}-1]$ and
By Lemma 2.1, we have $R_{C_{2l}}(n)=R_{D_{2l}}(n)$ for all $n\in \mathbb{N}$, the sets $C_{2l}$ and $D_{2l}$ partition the interval $[0, 2m_{2l-1}-1]=[0, 2^{2l+1}-1]=[0, m_{2l}+1]$. In addition, it is easily seen that $\{0, m_{2l}\}\subseteq C_{2l}$ and $\{1, m_{2l}+1\}\subseteq D_{2l}$. Then
By Lemma 2.1, we have $R_{C_{2l+1}}(n)=R_{D_{2l+1}}(n)$ for all $n\in \mathbb{N}$ and
Applying again Lemma 2.1, we can conclude that $R_{C_{i}}(n)=R_{D_{i}}(n)$ for all $n\in \mathbb{N}$, $C_{i}\cup D_{i}=[0, m_{i}-1]$ and $C_{i}\cap D_{i}=\{m_{2l}, m_{2l}+1\}+\{0, m_{2l+1}, \ldots, (2^{i-2l}-1)m_{2l+1}\}$ for each $i\geq 2l+1$.
Therefore, by the definitions of C and D in (3.1)–(3.3), we have $R_{C}(n)=R_{D}(n)$ for all $n\in \mathbb{N}$, $C\cup D=\mathbb{N}$ and
(Necessity). To prove the necessity of Theorem 1.3, we need the following three claims.
Claim 1.
Given $0 \lt r_{1} \lt r_{2}\leq m$, there exists at most one pair of sets (C, D) such that $C\cup D=\mathbb{N}$, $C\cap D=(r_{1}+m\mathbb{N})\cup (r_{2}+m\mathbb{N})$ and $R_{C}(n)=R_{D}(n)$ for all $n\in\mathbb{N}$.
Proof of Claim 1
Assume that there exist at least two pairs of sets (C, D) and $(C', D')$ which satisfy the conditions
We may assume that $0\in C\cap C'$. Let k be the smallest positive integer such that $\chi_{C}(k)\neq\chi_{C'}(k)$. Write
Then
For any integer $n\in [0, k]$, by the hypothesis, we have
Thus there exist two pairs of sets $(C_{1}, D_{1})$ and $(C_{2}, D_{2})$ satisfying (3.4)–(3.8). By Lemma 2.2, this is impossible. This completes the proof of Claim 1.
Claim 2.
Let $r_{1}, r_{2}, m$ be integers with $0 \lt r_{1} \lt r_{2} \lt r_{1}+r_{2}\leq m$ and $2\mid r_{1}$. Let C and D be sets of non-negative integers such that $C\cup D=[0, m]$, $C\cap D=\{r_{1}, r_{2}\}$ and $0\in C$. If $R_{C}(n)=R_{D}(n)$ for any integer $n\in [0, m]$, then there exists a positive integer l such that $r_{1}=2^{2l+1}-2, r_{2}=2^{2l+1}-1$.
Proof of Claim 2
Let
Then
Since $R_{C}(n)=R_{D}(n)$ for any integer $n\in [0, m]$, we have
Noting that $C\cup D=[0, m]$, $C\cap D=\{r_{1}, r_{2}\}$, we have
Then
Thus
An easy calculation shows that $r_{1}\geq 6$, $\{0, 3, 5, 6\}\subset C$ and $\{1, 2, 4, 7\}\subset D$.
In order to prove $r_{2}=r_{1}+1$, we suppose that $r_{2}\geq r_{1}+2$ and we will show that this leads to a contradiction.
The coefficient of $x^{r_{1}-1}$ in (3.12) is $0=2\sum\limits_{i=0}^{r_{1}-1}\chi_{C}(i)-r_{1}$. Since $r_{1}\in C$, we have $\chi_{C}(r_{1})=1$. Then $2\sum\limits_{i=0}^{r_{1}}\chi_{C}(i)=r_{1}+2$. The coefficient of $x^{r_{1}}$ in (3.12) is $2\chi_{C}\big(\frac{r_{1}}{2}\big)=2\sum\limits_{i=0}^{r_{1}}\chi_{C}(i)-r_{1}=2$. Then $\chi_{C}\big(\frac{r_{1}}{2}\big)=1$. The coefficient of $x^{r_{1}+1}$ in (3.12) is $0=2\sum\limits_{i=0}^{r_{1}+1}\chi_{C}(i)-r_{1}-4=2\chi_{C}(r_{1}+1)-2$. Then $\chi_{C}(r_{1}+1)=1$. The coefficient of $x^{r_{1}+2}$ in (3.12) is $2\chi_{C}\big(\frac{r_{1}+2}{2}\big)=2\sum\limits_{i=0}^{r_{1}+2}\chi_{C}(i)-r_{1}-4$. Then $\chi_{C}\big(\frac{r_{1}+2}{2}\big)=\chi_{C}(r_{1}+2)$. If $r_{2}=r_{1}+2$, then $\chi_{C}(r_{1}+2)=1$. Comparing the coefficients of $x^{r_{1}+s}$ with $s\in \{3, 4, 5\}$ on the both sides of (3.12), we have
Then $\chi_{C}(r_{1}+3)=0$, $\chi_{C}(r_{1}+4)=1$ and $\chi_{C}(r_{1}+5)=-1$, a contradiction. Thus $r_{2}\geq r_{1}+3$. The coefficient of $x^{r_{1}+3}$ in (3.12) is
Then $\chi_{C}(r_{1}+2)=\chi_{C}(r_{1}+3)=0$. Thus $\chi_{C}\big(\frac{r_{1}+2}{2}\big)=0$ and $r_{2}\geq r_{1}+4$. The coefficient of $x^{r_{1}+4}$ in (3.12) is
Then $\chi_{C}(r_{1}+4)=1$, $\chi_{C}\big(\frac{r_{1}+4}{2}\big)=0$ and $2\sum\limits_{i=0}^{r_{1}+4}\chi_{C}(i)=r_{1}+6$. By Lemma 2.2, we have
Since $\chi_{C}\big(\frac{r_{1}+2}{2}\big)=\chi_{C}\big(\frac{r_{1}+4}{2}\big)$ and $\frac{r_{1}+4}{2}\leq r_{1}-1$, by (3.13) and the definition of A, we have $r_{1}\equiv 0\pmod 4$. It follows that $r_{1}\geq 8$ and $\chi_{C}\big(\frac{r_{1}+6}{2}\big)=1$.
Let k be a positive even integer such that $r_{1}\leq k \lt k+1 \lt \min\{r_{2}, 2r_{1}\}\leq m$. Comparing the coefficients of x k and $x^{k+1}$ on the both sides of (3.12) respectively, we have
Subtracting the above two equalities and dividing by 2 we can get
Since $k+1-r_{1} \lt r_{1}, k-r_{1}$ is even, by (3.13), we have
If $\chi_{C}(k-r_{1})=0$, then $\chi_{C}(k+1-r_{1})=1$. By (3.14), we get $\chi_{C}(\frac{k}{2})=0$. If $\chi_{C}(k-r_{1})=1$, then $\chi_{C}(k+1-r_{1})=0$. By (3.14), we get $\chi_{C}(\frac{k}{2})=1$. Thus
If $\min\{r_{2}, 2r_{1}\} \gt 2r_{1}-1$, then choose $k=2r_{1}-2^{i+1}$ with $i\geq 0$ in (3.15), we have
Then
By Lemmas 2.3 and 2.4, we have $r_{1}=2^{\lceil\log_{2}r_{1}\rceil}-1$, which contradicts $2\mid r_{1}$.
If $r_{2}=2r_{1}-1$, then compare the coefficients of $x^{r_{2}}$ and $x^{r_{2}-1}$ on the both sides of (3.12) respectively, we have
Then $2\chi_{C}(r_{1}-1)=\chi_{C}(r_{1}-2)$. It follows that $\chi_{C}(r_{1}-2)=\chi_{C}(r_{1}-1)=0$, which contradicts $\chi_{C}(r_{1}-2)+\chi_{C}(r_{1}-1)=1$. Thus $r_{2}\leq 2r_{1}-2$.
Let k be a non-negative integer such that $2r_{1}\leq 2r_{1}+k \lt 2r_{1}+k+1 \lt r_{1}+r_{2}\leq m$. If k is even, then compare the coefficients of $x^{2r_{1}+s}$ with $s\in \{k, k+1\}$ on the both sides of (3.12), we have
Subtracting the above two equalities and dividing by 2 we can get
If k is odd, then compare the coefficients of $x^{2r_{1}+s}$ with $s\in \{k, k+1\}$ on the both sides of (3.12), we have
Subtracting the above two equalities and dividing by 2 we can get
If r 2 is even, then choose k = 0 and k = 2 in (3.16) respectively, we have
Then
By (3.13), we have $\chi_{C}(2r_{1}-r_{2})+\chi_{C}(2r_{1}+1-r_{2})=1$ and $\chi_{C}(2r_{1}+2-r_{2})+\chi_{C}(2r_{1}+3-r_{2})=1$. Then $\chi_{C}(2r_{1}-r_{2})=1$ and $\chi_{C}(2r_{1}+2-r_{2})=1$. It follows that $r_{2}\equiv 2\pmod 4$. The coefficient of $x^{r_{2}}$ in (3.12) is
and the coefficient of $x^{r_{2}+1}$ in (3.12) is
Then
By $\chi_{C}(r_{2}-r_{1})+\chi_{C}(r_{2}+1-r_{1})=1$, we have $\chi_{C}(r_{2}-r_{1})=0$, $\chi_{C}(r_{2}+1-r_{1})=1$. By $r_{1}\equiv 0\pmod 4$ and $r_{2}\equiv 2\pmod 4$, we have $\chi_{C}(r_{2}-1-r_{1})=0$, $\chi_{C}(r_{2}-2-r_{1})=1$. The coefficient of $x^{r_{2}-1}$ in (3.12) is
Then $2\sum\limits_{i=0}^{r_{2}-1}\chi_{C}(i)=r_{2}+2$. It follows that $2\sum\limits_{i=0}^{r_{2}}\chi_{C}(i)=r_{2}+4$ and $\chi_{C}\big(\frac{r_{2}}{2}\big)=1$. The coefficient of $x^{r_{2}-2}$ in (3.12) is
Then $\chi_{C}\big(\frac{r_{2}-2}{2}\big)=2-\chi_{C}(r_{2}-1)$. Thus $\chi_{C}\big(\frac{r_{2}-2}{2}\big)=\chi_{C}(r_{2}-1)=1$. By (3.13) and $\chi_{C}\big(\frac{r_{2}-2}{2}\big)=\chi_{C}\big(\frac{r_{2}}{2}\big)=1$, we have $r_{2}\equiv 0\pmod 4$, a contradiction.
If r 2 is odd, then $r_{1}+5\leq r_{2}\leq 2r_{1}-3$. The coefficient of $x^{r_{1}+5}$ in (3.12) is
Then $\chi_{C}(r_{1}+5)=0$ and so $r_{2}\geq r_{1}+7$. The coefficient of $x^{r_{1}+6}$ in (3.12) is
Then $\chi_{C}(r_{1}+6)=\chi_{C}\big(\frac{r_{1}+6}{2}\big)=1$. By choosing k = 3 and k = 5 in (3.17) respectively, we have
Then
By (3.13), we have $\chi_{C}(2r_{1}+4-r_{2})+\chi_{C}(2r_{1}+3-r_{2})=1$ and $\chi_{C}(2r_{1}+6-r_{2})+\chi_{C}(2r_{1}+5-r_{2})=1$. Then $\chi_{C}(2r_{1}+3-r_{2})=\chi_{C}(2r_{1}+5-r_{2})=1$. Applying again (3.13), we have $r_{2}\equiv 1\pmod 4$. The coefficient of $x^{2r_{1}-2}$ in (3.12) is
and the coefficient of $x^{2r_{1}-1}$ in (3.12) is
Subtracting the above two equalities and dividing by 2 we can obtain
Noting that $\chi_{C}(r_{1}-2)+\chi_{C}(r_{1}-1)=1$ and $\chi_{C}(2r_{1}-2-r_{2})=\chi_{C}(2r_{1}-1-r_{2})$, we have $3\chi_{C}(r_{1}-1)=2-\chi_{C}(2r_{1}-1)$. However, it is impossible. Therefore $r_{2}=r_{1}+1$.
The remainder of the proof is similar to the proof of [Reference Sun and Pan13, Theorem 1.1]. For the sake of completeness we give the details.
Let k be a positive even integer with $r_{2} \lt k \lt k+1 \lt 2r_{1} \lt r_{1}+r_{2}\leq m$. Comparing the coefficients of $x^{k-1}, x^{k}$ and $x^{k+1}$ on the both sides of (3.12) respectively, we have
Calculating the above three equalities, we have
By choosing $k=2r_{1}-2$ in (3.19), we have
Then $\chi_{C}(r_{1}-1)=\chi_{C}(r_{1}-3)$. Thus $r_{1}\equiv 2\pmod 4$ and $r_{2}\equiv 3\pmod 4$.
If $k-1-r_{2}\equiv 0\pmod 4$, then $k-r_{1}\equiv 2\pmod 4$ and $k\equiv 0\pmod 4$. Thus
Hence
If $\chi_{C}(k-1-r_{2})=0$, then $\chi_{C}(k-r_{1})=1$. By (3.18), we have $\chi_{C}(\frac{k}{2})=1$. If $\chi_{C}(k-1-r_{2})=1$, then $\chi_{C}(k-r_{1})=0$. By (3.18), we have $\chi_{C}(\frac{k}{2})=0$. Thus $\chi_{C}\big(\frac{k}{2}\big)=\chi_{C}(k-r_{1})$ and $\chi_{C}\big(\frac{k}{2}\big)+\chi_{C}(k-1-r_{2})=1$. Noting that $\chi_{C}(k-1-r_{2})+\chi_{C}(k-r_{2})=1$, we have $\chi_{C}\big(\frac{k}{2}\big)=\chi_{C}(k-r_{2})$.
If $k-1-r_{2}\equiv 2\pmod 4$, then $k-r_{1}\equiv 0\pmod 4$ and $k\equiv 2\pmod 4$. By (3.18), we have
Then $\chi_{C}\big(\frac{k-2}{2}\big)=\chi_{C}(k-2-r_{1})$. Noting that $\chi_{C}\big(\frac{k-2}{2}\big)+\chi_{C}\big(\frac{k}{2}\big)=1$ and $\chi_{C}(k-1-r_{2})+\chi_{C}(k-r_{2})=1$, we have $\chi_{C}\big(\frac{k}{2}\big)=\chi_{C}(k-r_{2})$.
As a result, we can obtain $\chi_{C}\big(\frac{k}{2}\big)=\chi_{C}(k-r_{2})$. Put $k=2r_{2}-2^{i+1}$ with $i\geq 0$. Then $\chi_{C}(r_{2}-2^{i})=\chi_{C}(r_{2}-2^{i+1})$. Thus
By Lemma 2.3, we have $r_{1}=2^{2l+1}-2$ and $r_{2}=2^{2l+1}-1$ for some positive integer l.
This completes the proof of Claim 2.
Claim 3.
Let l be a positive integer and let $E, F$ be two sets of non-negative integers with $E\cup F=[0, 3 \cdot 2^{2l+1}-4], 0\in E$ and $E\cap F=\{2^{2l+1}-2, 2^{2l+1}-1\}$. Then $R_{E}(n)=R_{F}(n)$ for any integer $n\in [0, 3\cdot 2^{2l+1}-4]$ if and only if
Proof of Claim 3.
We first prove the sufficiency of Claim 3. It is easy to verify that $E\cup F=[0, 3 \cdot 2^{2l+1}-4]$, $0\in E$ and $E\cap F=\{2^{2l+1}-2, 2^{2l+1}-1\}$.
If $n\in [0, 2^{2l+2}-3]$, then
and
By Lemma 2.5, for all $k\in\mathbb{N}$, we have $R_{A_{2l+1}}(k)=R_{B_{2l+1}}(k)$. Then $R_{E}(n)=R_{F}(n)$.
If $n\in [2^{2l+2}-2, 3\cdot 2^{2l+1}-5]$, then
and
By Lemma 2.5, $R_{A_{2l+1}}(k)=R_{B_{2l+1}}(k)$ holds for all $k\in\mathbb{N}$ and then $R_{E}(n)=R_{F}(n)$.
By $3\cdot 2^{2l+1}-4=(2^{2l+1}-2)+(2^{2l+2}-2)$ in D, we have
and
Thus $R_{C}(3\cdot 2^{2l+1}-4)=R_{D}(3\cdot 2^{2l+1}-4)$.
The necessity of Claim 3 follows from Lemma 2.2 and the sufficiency of Claim 3.
This completes the proof of Claim 3.
Now let
Then
Moreover, for any integer $n\in [0, m-1+r_{1}]$, we have
Thus for any integer $n\in [0, m-1+r_{1}]$, we have
Noting that $r_{2}\leq m-1$, we see that $r_{1}+r_{2}\leq m-1+r_{1}$. By Claim 2, there exists a positive integer l such that $r_{1}=2^{2l+1}-2, r_{2}=2^{2l+1}-1$.
Let E and F be as in Claim 3. If $m\geq 2^{2l+2}-1$ and $0\in C$, then $m-1+r_{1}\geq 3\cdot 2^{2l+1}-4$ and
Moreover, $R_{C(3 \cdot 2^{2l+1}-4)}(n)=R_{C}(n)=R_{D}(n)=R_{D(3 \cdot 2^{2l+1}-4)}(n)$ for all $n\in [0, 3 \cdot 2^{2l+1}-4]$. By Lemma 2.2, we have
By
we know that $R_{C}(3\cdot 2^{2l+1}-3)=R_{D}(3\cdot 2^{2l+1}-3)$ if and only if $\chi_{C}(3\cdot 2^{2l+1}-3)=0$, that is, $3\cdot 2^{2l+1}-3 \in D$. Noting that $2^{2l+1}-2\in A_{2l+1}, 2^{2l+1}-1\in B_{2l+1}$, $3\cdot 2^{2l+1}-2=(2^{2l+1}-1)+(2^{2l+2}-1)$ in C and $3\cdot 2^{2l+1}-2=1+(3\cdot 2^{2l+1}-3)$ in D, we obtain
and
Thus by Lemma 2.5, we have $R_{C}(3\cdot 2^{2l+1}-2) \gt R_{D}(3\cdot 2^{2l+1}-2)$, which is impossible. Therefore $m\leq 2^{2l+2}-2$.
Now we assume that $2^{2l+1} \leq m\leq 2^{2l+2}-3$ and $0\in C$. Let
Since $2^{2l+2}-2\leq M\leq 3\cdot 2^{2l+1}-5$, by Lemma 2.2, we have
Moreover,
Since $R_{C}(n)=R_{D}(n)$ for all $n\in\mathbb{N}$ and $0\not\in D$, we have
for any integer $n\in [0, M]$. By (3.20)–(3.23) and Lemma 2.2, we have
Then $\chi_{E}(M)=1$, $\chi_{F}(M)=0$.
By $2^{2l+1}-3\in A_{2l+1}$, we have $3\,\cdot\,2^{2l+1}-5\in F$. Then $M \lt 3\,\cdot\,2^{2l+1}-5$. If $\chi_{E}(M+1)=1$, then $\chi_{F}(M+1)=0$ and $C(M+1)=E(M+1), D(M+1)=F(M+1)\cup \{M, M+1\}$. Thus
and
By Claim 3, we have $R_{E(M+1)}(M+1)=R_{F(M+1)}(M+1)$. Then $R_{C}(M+1)\neq R_{D}(M+1)$, a contradiction. Thus $\chi_{E}(M+1)=0$ and $\chi_{F}(M+1)=1$.
Let t be an arbitrary positive integer such that $M \lt M+t \lt M+t+1\leq 3\cdot 2^{2l+1}-4$. Then $1\leq t\leq 2^{2l+1}-3$. Define the sets S and T by
Noting that
we have
Then
It follows that
For $M+t\leq n\leq 3\cdot 2^{2l+1}-4$, let
We claim that
In fact, if $E(M+t)\backslash C(M+t)=\emptyset$, then $N_{1}(t, n)=N_{2}(t, n)=0$; if
for some positive integer u, then by (3.24), we have $c_{i}\geq M+1$ and so $0\leq n-c_{i}\leq 2^{2l+1}-3$ for $i\in [1, u]$. In view of
we have
Thus (3.26) holds. Similarly, we can deduce (3.27) holds.
By $M+t \lt 3\cdot 2^{2l+1}-4 \lt 2^{2l+3}-4\leq 2M$, we can obtain
Similarly, we can get
By choosing $n=M+t$ and $n=M+t+1$ in (3.28) respectively, we have
and
By choosing $n=M+t$ and $n=M+t+1$ in (3.29) respectively, we have
and
Note that $R_{C(n)}(n)=R_{D(n)}(n)$ and $R_{E(n)}(n)=R_{F(n)}(n)$. By (3.30)–(3.33), we have
and
and
Then
If M is even, then we can write
where $b_{i}\in \{0, 1\}$. It follows from $\chi_{F}(M)=0$ that $\chi_{B_{2l+1}}\big(\sum\limits_{i=1}^{2l}b_{i}2^{i}\big)=1$. By choosing $M+t+1=3\cdot 2^{2l+1}-4$ in (3.34), we see that t is odd and
Then $\chi_{E}(t+1)=0$. It follows from $\chi_{F}(t)+\chi_{E}(t)=1$ and $\chi_{E}(3\cdot 2^{2l+1}-4)=1$ that $\chi_{E}(t-1)=0$ and $\chi_{F}(t-1)=1$. Since $\chi_{E}(t-1)+\chi_{E}(t)=1$, we have $\chi_{E}(t)=1$ and $\chi_{F}(t)=0$. Noting that $\chi_{E}(t-1)=\chi_{E}(t+1)$, we have $t\equiv 3\pmod 4$ and so $t\geq 3$. Then $\chi_{E}(t-2)=0$. By choosing $M+(t-1)+1=3\cdot 2^{2l+1}-5$ in (3.34), we have
It follows from $\chi_{E}(M+(t-1)+1)=\chi_{E}(3\cdot 2^{2l+1}-5)=0$ that $\chi_{C}(M+(t-1)+1)=-1$, which is clearly false.
If M is odd, then we can write
where $f\in\{0, 1, \ldots, 2l-1\}$ and $b_{i}\in \{0, 1\}$. It follows from $\chi_{E}(M+1)=0$ and $\chi_{F}(M)=0$ that
Then f is odd. By choosing $M+t+1=3\cdot 2^{2l+1}-4$ in (3.34), we see that t is even and
Then $\chi_{E}(t+1)=0$ and $\chi_{F}(t)=0$. Thus $\chi_{E}(t)=1$. It follows from $\chi_{E}(3\cdot 2^{2l+1}-4)=1$ that $\chi_{E}(t-1)=0$ and $\chi_{F}(t-1)=1$. Since $\chi_{E}(t-1)=\chi_{E}(t+1)$, we have $t\equiv 0\pmod 4$ and so $t\geq 4$. Then $\chi_{E}(t-2)=\chi_{E}(t-3)=1$ and $\chi_{F}(t-2)=0$. By choosing $M+(t-2)+1=3\cdot 2^{2l+1}-6$ in (3.34), we have
It follows from $\chi_{E}(M+(t-2)+1)=\chi_{E}(3\cdot 2^{2l+1}-6)=1$ that $\chi_{C}(M+(t-2)+1)=2$, which is also impossible. Therefore $m=2^{2l+2}-2$.
This completes the proof of Theorem 1.3.
Acknowledgements
This work was supported by the National Natural Science Foundation of China (Grant No. 12371003).